2018
DOI: 10.1177/0265407518814371
|View full text |Cite
|
Sign up to set email alerts
|

A socioecological perspective to understanding mental and physical health: The mediating role of relationship mindsets and goals

Abstract: People’s mindsets and goals regarding social relationships affect their relationship quality and psychological well-being. We employed multiple group path modeling to examine how perceived relational mobility affects mental and physical health through relationship mindsets (destiny and growth mindsets) and relationship goals (approach and avoidance goals) across countries, surveying community adults in the U.S. ( n = 206; Mage = 39.14; 48% female) and South Korea ( n = 236; Mage = 38.89; 51% female) through on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Likewise, the freedom to determine what to choose may also lead to an increased belief of personal control on life events (Genschow, Rigoni, & Brass, 2017) and an obligation to regulate one’s behaviours (e.g., expressing less ethnic prejudice; Zhao, Liu, Zhang, Shi, & Huang, 2014). Supporting our argument, empirical evidence has shown that RM was associated with a growth mindset that relationships can be cultivated through efforts (Lee et al, 2019). RM has also been found to predict dispositional sense of control.…”
Section: A Socioecological Understanding Of the Effect Of Mobility Onsupporting
confidence: 78%
See 4 more Smart Citations
“…Likewise, the freedom to determine what to choose may also lead to an increased belief of personal control on life events (Genschow, Rigoni, & Brass, 2017) and an obligation to regulate one’s behaviours (e.g., expressing less ethnic prejudice; Zhao, Liu, Zhang, Shi, & Huang, 2014). Supporting our argument, empirical evidence has shown that RM was associated with a growth mindset that relationships can be cultivated through efforts (Lee et al, 2019). RM has also been found to predict dispositional sense of control.…”
Section: A Socioecological Understanding Of the Effect Of Mobility Onsupporting
confidence: 78%
“…However, Yuki et al (2013) also revealed no causal impact of RM on subjective well‐being (Yuki et al, 2013, Study 3), but their manipulation of RM (in a high‐RM condition [recalling talking with a stranger] vs. a low‐relational‐mobility condition [talking with a family member]) may be confounded with a feeling of familiarity, which boosted subjective well‐being in the low‐RM condition. As we have illustrated, high RM leads to a growth mindset of relationality (Lee et al, 2019); therefore, it may further result in a tendency to focus on positive relationships and disregard negative ones. For exploration, we also predicted that participants in a high‐relational‐mobility environment may also estimate that they would have more friends and less enemies than would those in a low‐relational‐mobility environment.…”
Section: A Socioecological Understanding Of the Effect Of Mobility Onmentioning
confidence: 85%
See 3 more Smart Citations